The Synergicity Of Essentially The Identity Of God In The Vedic Teaching And The Siwatattwa As Guidelines For Hindureligious Practices In Bali - I Wayan Ardhi Wirawan; I Gede Sura; Ketut Wardana (Jayapangus Press, 2020)
This research aims to study the essential synergy of divine identity in the Vedic scriptures and the Siwatattwa teachings. The divine identity which is the focus of this research is based on the reason for the development of the discourse